Contraceptive Usage in Female Survivors of Young Adult Cancers [17F]. (May 2018) - Shandley, Lisa M.; Spencer, Jessica B.; McKenzie, Laurie J.; Mertens, Ann C.; Howards, Penelope P.
Abstract : INTRODUCTION: Cancer survivors may be less likely than the general population to use effective methods of contraception, but prior studies were small. METHODS: In a population-based study, we recruited reproductive-aged (22-45 years) women, diagnosed with cancer between the ages of 20-35 years and at least 2 years post-diagnosis. Women with no cancer history were recruited for comparison. Exclusion criteria included having a hysterectomy or bilateral oophorectomy. Women reported on contraceptive use (pills, patch, ring, mini-pills, Depo Provera, implant, hormonal and non-hormonal intrauterine device, and tubal ligation) in the past year. RESULTS: Among survivors (n=960), 38.4% reported using a WHO Tier I/II contraceptive method in the past year compared to 47.5% of comparison women (n=992). Long-acting reversible contraceptive (LARC) was more common among contracepting survivors (30.9%) than among contracepting comparison women (23.4%). Among cancer survivors contraceptive use was associated with being younger than 35 years at interview (odds ratio [OR]: 2.04, 95% confidence interval [CI] 1.55, 2.67), being younger than 30 years at diagnosis (OR 1.81, 95% CI 1.38, 2.37), identifying as white (OR 1.54, 95% CI 1.13, 2.10), not having chemotherapy (OR 1.43, 95% CI 1.10, 1.86), and being nulligravid at cancer diagnosis (OR 1.31, 95% CI 1.01, 1.69). Breast cancer survivors were less likely to have used birth control in the past year (OR 0.46, 95% CI 0.34, 0.62) compared with all other cancer types. CONCLUSION: While the overall rate of contraceptive use was lower among cancer survivors than among comparison women, survivors using contraception were more likely to use LARC methods.